Penyelarasan Hukum Investasi Dan Hukum Dagang Di Negara-Negara Asean - Syafitri, Nanda; Siregar, Emiel Salim; Pratiwi, Cindy; Ridho, Muhammad; Siahaan, Siti Khodijah; Wahyuni, Devi Sri; Afni, Nurul (Jurnal Ilmiah Wahana Pendidikan, 2024)
Regional integration , especially the economic side has proved to be a kind of vital passport to economic development. Several opinions and theories have been put forward by exponents of this highly controversial issue to be selected by states actors appropriate to their national goals. At present there is a general awareness that economic cooperation requires the development of a harmonious relationship between economic and political policies both at the national and multinational level. What should be emphasized is that in order to encourage economic cooperation among the ASEAN countries as a means of enhancing the rate of economic development, there should be a radical changed in the role of politics to ensure that it contribute positively to economic cooperation. Mindful of the economic,sosial, political and legal fragmentation prevail in the ASEAN countries, the harmonization of investment and trade laws is a prerequisite to economic integration for the regional cooperation in Southeast Asia in the future.